BUILDING THE CHARACTER OF GENERATION Z THROUGH DIGITAL LITERACY-BASED ISLAMIC EDUCATION - Kuswantoro; Gun Gun Gunawan; Kanafi; Mucharror; Multazom (PT. Cadas Insan Madani, 2026)
Character development has become one of the primary concerns in contemporary education, particularly in response to the complex social and ethical challenges faced by Generation Z in the digital era. The widespread use of digital technologies has transformed the way young people access information, communicate, and construct their personal and religious identities, creating both opportunities and risks for character formation. This study aims to examine the role of digital literacy-based Islamic education in building the character of Generation Z and to identify effective strategies for its implementation in contemporary educational settings. This research employs a qualitative library research approach using content analysis of books, scholarly articles, policy documents, and previous studies related to Islamic education, digital literacy, and character education. The findings reveal that integrating digital literacy with Islamic educational values contributes significantly to developing critical thinking, ethical digital citizenship, responsibility, honesty, empathy, tolerance, and religious moderation among Generation Z. Islamic values such as akhlaq (moral character), amanah (trustworthiness), hikmah (wisdom), and wasatiyyah (moderation) provide a strong ethical foundation for responsible digital engagement while reinforcing students' moral and spiritual identities. Furthermore, effective implementation requires innovative learning strategies, the integration of digital technologies into Islamic education, and collaborative support from educators, families, and communities. The study concludes that digital literacy-based Islamic education offers a comprehensive and sustainable framework for strengthening Generation Z's character, enabling them to become morally responsible, digitally literate, and socially engaged citizens capable of responding to the challenges of the digital age.